2009
DOI: 10.1177/175045890901900603
|View full text |Cite
|
Sign up to set email alerts
|

Use of Drains in Surgery: A Review

Abstract: Drains have been used in surgery for several years to remove body fluids thereby preventing the accumulation of serous fluid and improving wound healing. Drains may be classified as closed or open systems, and active or passive depending on their intended function. Closed vacuum drains apply negative suction in a sealed environment, producing apposition of tissues and thus promoting healing. Correct assessment of clinical indications might reduce unnecessary usage. This article will introduce the principles an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 35 publications
1
35
1
5
Order By: Relevance
“…The drains are removed when the volume is ≤ 25 ml over a 24-h period (~1 ml/h). 5,6 In our experience, this measurement reflects drainage rates inaccurately. Factors such as the time of completion of surgery and expected accumulation of fluid in the dissected tissue spaces in the immediate postoperative period are not taken into consideration.…”
mentioning
confidence: 99%
“…The drains are removed when the volume is ≤ 25 ml over a 24-h period (~1 ml/h). 5,6 In our experience, this measurement reflects drainage rates inaccurately. Factors such as the time of completion of surgery and expected accumulation of fluid in the dissected tissue spaces in the immediate postoperative period are not taken into consideration.…”
mentioning
confidence: 99%
“…The ability to effectively remove fluid more completely could potentially reduce complications traditionally associated with flap elevation and even facilitate patient recovery (Durai, Mownah, & Ng, 2009). The ability to effectively remove fluid more completely could potentially reduce complications traditionally associated with flap elevation and even facilitate patient recovery (Durai, Mownah, & Ng, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…When drainage is employed, it should be efficiently used and removed at the earliest safe time following the surgery. Durai et al suggested that it was relatively safe to remove a drainage tube if the drainage flow was <25 ml within 24 h (20). In addition, drains should be placed carefully to avoid direct contact with the major blood vessels, organs and anastomoses, and should be withdrawn and turned appropriately for a period of time (20).…”
Section: Discussionmentioning
confidence: 99%